Regional Differences in Sea Level Rise Between the Mid‐Atlantic Bight and the South Atlantic Bight: Is the Gulf Stream to Blame?. Issue 7 (13th July 2019) - Ezer, Tal
Abstract: Recent studies appear to show that a "hot spot" for accelerated sea level rise (SLR) shifted around 2010 from the Mid‐Atlantic Bight (MAB) to the South Atlantic Bight (SAB) and south Florida. The role of the Gulf Stream (GS) in this shift was thus investigated. The findings show that in the ~15–20 years before, SLR was accelerating in the MAB due to weakening and southward shifting of the GS. After 2010, however, SLR started slowing down in the MAB due to strengthening and northward shifting of the GS. Thermosteric effects seen in altimeter data indicate a warming trend south of 35°N that started around 2010 and contributed to increased SLR south of Cape Hatteras. However, in the MAB, after the GS separated from the coast, the warming of the Subtropical Gyre and cooling of nearshore waters resulted in an opposite SLR response and strengthening of the GS front. Oscillations with periods of 2–5 years dominated the GS flow and coastal sea level variability, but the GS in the MAB is often out of phase with the GS in the SAB due to eddies and recirculation gyres. These oscillations can create temporal changes in SLR rates that are ~10 times larger than the long‐term trend, so recent changes in the local "hot spot" may not be interpreted as a sign of a shift in the long‐term trend, but more likely a temporal shift associated with interannual and decadal variations in the North Atlantic. Plain Language Summary: Regional changes in sea level rise (SLR) rates along the U.S. East Coast and the role of the Gulf Stream (GS) in those changes are investigated, explaining why the largest SLR rates were found north of Cape Hatteras before 2010 and south of Cape Hatteras after 2010. Before 2010 SLR was accelerating in the MAB due to weakening and southward shifting of the GS, but after 2010 SLR started slowing down in the MAB due to strengthening and northward shifting of the GS. Because of the GS dynamics and its distance to shore, a warming trend south of 35°N that started around 2010 had different sea level response in the north and south. Oscillations with periods of 2–5 years were also investigated. Key Points: A recent shift in the location of a hot spot for accelerated sea level rise along the U.S. East Coast was investigated Changes in the Gulf Stream strength and position around 2010 seemed to explain the regional changes in coastal sea level Interannual and decadal variations in the Gulf Stream can contribute to temporal and spatial changes in sea level rise rates